What do parents need to know about concussion? Developing consensus using the delphi method - Kroshus, E.; Chrisman, S.; Harmon, K. G.; Herring, S. A.; Broglio, S. P.; Master, C. L.; McGill, C. A.; Putukian, M.; Register-Mihalik, J. K.; Rivara, F. P. (Clinical Journal of Sport Medicine, 2021)
Objective: Many schools and sports leagues provide preseason concussion education to parents/guardians, and in some jurisdictions, it is required for interscholastic sports participation. However, directives about content are absent or vague. The purpose of this study was to obtain expert consensus about what parents/guardians need to know to about concussion. Design: A modified Delphi process with nationally recognized expert panel members was used to obtain consensus about parent/guardian behaviors relevant to concussion prevention, identification, and management and knowledge domains relevant to performance of those behaviors. Results: Sixteen parent/guardian behaviors and 24 knowledge domains were identified. However, consensus was not achieved regarding whether it is realistic to expect parents/guardians to perform approximately one-third of the behaviors that experts agreed mattered. This variability may reflect underlying uncertainty about the capacities of some parents/guardians to put knowledge into action or the belief that there are other barriers to action. Furthermore, for most knowledge domains, there was a lack of agreement about whether or not there could be a "correct" answer on the basis of current scientific knowledge. Conclusions: These findings raise practical and ethical questions: how can we expect parents/guardians to help prevent, identify, or manage concussion if they cannot have all the information required to engage in these behaviors due to lack of scientific consensus? This issue is not unique to concussion. Best practices for risk communication and shared decision-making can inform how we think about educating parents/guardians about concussion inside and outside of the health care setting.